Znanstveni predmet sociologije kulture - Kržan, Marko (Ars et humanitas, 2013)
This article outlines the scientific object of the sociology of culture. The starting points are two intuitive objects of this discipline: the cultural sphere as it presents itself to naive observation, and the methodologically motivated notion that culture/ consciousness is the constitutive aspect of all social phenomena. The article attempts to produce a dialectical synthesis of these opposing positions. It starts with Marcel Mauss's "total social fact", the notion that every social fact is a unity of structure and representation. However, to explain the "cultural" phenomena, the sociology of culture must be able to grasp the specificity of those total social facts that also function as representations in relation to other, "non-cultural" social facts. Such ideological practices or forms of consciousness are its true object. The article goes on to establish the criteria for classifying the ideological and the material social facts as parts of the Marxian base or superstructure. It argues that the formal criterion - type of social relations - is necessary and sufficient for determining to which mode of production a certain material practice belongs. The formal criterion, though, is not sufficient when it comes to ideological practices: from the formal viewpoint, many ideological practices belong to the base of the capitalist mode of production. However, because of their function, they must also be analysed as parts of its superstructure.
Keywords: sociologija kulture; marksizem; Marxism; ideologija; produkcijski načini